2012
DOI: 10.1080/00397911.2011.585267
|View full text |Cite
|
Sign up to set email alerts
|

Polycondensation of Sebacic Acid with Primary and Secondary Hydroxyl Groups Containing Diols Catalyzed by Candida antarctica Lipase B

Abstract: The aliphatic polyesters are normally synthesized by ester interchange reactions or direct esterification of hydroxyacids or diacid/diol combinations. Biotransformation, utilizing the enzymes as catalysts, was accepted as an alternative route for the synthesis of aliphatic polyesters and offers various advantages compared with the conventional, metal-catalyzed polymerization reactions. Previous studies indicated that lipase-catalyzed polycondensation reactions between diols and diacids occurred preferentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…The first assumption is supported by the CALB higher reactivity toward primary hydroxyls than the secondary ones. 34 36 The second assumption is supported by the work performed by Kline et al 20 and by Godinho et al, 66 in which cyclic end groups were not observed and some degree of cyclization was only observed for tetramers, respectively, for glycerol-based polyesters prepared via CALB catalysis.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The first assumption is supported by the CALB higher reactivity toward primary hydroxyls than the secondary ones. 34 36 The second assumption is supported by the work performed by Kline et al 20 and by Godinho et al, 66 in which cyclic end groups were not observed and some degree of cyclization was only observed for tetramers, respectively, for glycerol-based polyesters prepared via CALB catalysis.…”
Section: Resultsmentioning
confidence: 86%
“… 33 CALB is an sn -1,3-specific lipase with higher reactivity toward primary hydroxyls than secondary ones. 34 36 It is capable of hindering the crosslinking of polyesters prepared from glycerol and diacids/diesters, even at a relatively high molecular weight, and of catalyzing one-pot polymerization at mild reaction conditions. 27 , 29 Moreover, its specificity and reactivity could be modulated through the control of reaction parameters such as temperature 22 , 25 , 31 and solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly, the immobilized CALB catalyst is Novozym 435 (N435), a commercial product of Novozymes. N435-catalyzed synthesis of glycerol polyesters is usually performed by a one-pot synthetic method [ 70 , 71 , 72 ]. Lang et al described a family of poly(glycerol sebacate) (PGS) analogs where glycerol was replaced in part with octanediol (O) in bulk copolymerizations [ 68 ].…”
Section: Polyol Polyesters From Glycerol and Sugar Alcohols (Alditmentioning
confidence: 99%
“…Poly(L-lactic acid), poly(3-caprolactone), poly(glycolic acid), poly(trimethylene carbonate), poly(hydroxybutyrate), and so forth, constitute an important class of biodegradable polymers, which have signicant potential in agricultural sanitary elds, packaging applications, and bioengineering. [3][4][5][6][7][8][9] Usually, bio-based diacid and diol monomers are used to synthesize the aliphatic polyesters. 10,11 Compared with longchain aliphatic acids, short-chain aliphatic acids are prone to intra-molecular condensation reactions which would inuence the molecular weights and the polymer distribution.…”
Section: Introductionmentioning
confidence: 99%